POTENSI KOMBINASI KAPUR SIRIH DAN DAUN KUMPAI MAHUNG (Eupatorium inulifolium H.B&K.) SEBAGAI ALTERNATIF SALEP ANTI INFLAMASI ALAMI - Dwi Rizki Febrianti; Siska Musiam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Kumpai Mahung (Eupathorium inulifolium H.B & K) is one of an endemic plant in South Kalimantan. Hereditary used as traditional medicine. kapur sirih (calcium carbonate) is also used by the community as a food additive (BTP), especially in the manufacture of chips and fruit ice. Traditionally these two ingredients are combined to treat swollen (oedema) mastitis in nursing mothers. This research method using raw test pad oedema in legs male rats. simple ointment dosage form, induction carrageenan 3% and hydrocortisone as a positive control anti-inflammatory calculated the value and the value AUC (area under the curve). the results expressed Ointment combination Kumpai Mahung leaf extract and calcium carbonate have anti-inflammatory power of 14.91% greater than the positive control 9.95%.